The Association Between Metabolic Syndrome and Gastric Cancer in Chinese - Li, Fangxuan; Du, Hui; Li, Shixia; Liu, Juntian (Frontiers in Oncology, 2018)
Background: Metabolic syndrome(MetS) play a carcinogenic role in variety of cancers and influence the prognosis of cancer patients both systemically and hormonally. Methods: The data of clinicopathologic features and MetS of 808 gastric cancer patients and 1146 randomly healthy controls were analyzed retrospectively. Results: Higher TG level, lower HDL-C level and higher hypertension frequency were observed in all gastric cancer patients when compared with healthy controls. While, gastric cancer patients had greater waist circumference only in females. Among three definitions of MetS, the MetS identified by the Chinese Diabetes Society(CDS) was associated with the most significant increasing risk of gastric cancer. Comparing all gastric cancer patients with healthy controls, OR of gastric cancer was enhanced by various individual components of the MetS, including higher TG level, lower HDL-C level, hypertension and diabetes; In male subgroup, OR of gastric cancer was enhanced by higher BMI, hypertension and diabetes; In females, OR of gastric cancer was enhanced by lower HDL-C, hypertension and diabetes. MetS was associated with poor differentiated carcinoma, more advanced pathological T, N stage and TNM stage of gastric cancer. Conclusion: The presence of MetS and its components were increased in gastric cancer, especially in gastric cancer patients with poor differentiation and advanced stage, which implies that metabolic disorder may play an important role in the development of gastric cancer.